(untitled) (Journal of Contemporary Studies, 2025)
Russia’s multi-front invasion of Ukraine failed to achieve a quick and decisive victory. With its numerical and technological advantage, Russian armed forces were in an advantageous position against the Ukrainian counterparts. However, the high death toll and heavy equipment losses uncovered the technological deficiencies of Russian military forces. The article briefed the initial phase of the Russia-Ukraine war and how the territorial gains and losses occurred until April 2023. The article also discusses the technological limitations of Russian forces through the lens of Revolution in Military Affairs. A comparative evaluation of Russian and Ukrainian pre-war strength, as well as their combat losses, has also been provided. Analysis of Russian military limitations in the initial phase of the war is important as the majority of contemporary military forces still employ traditional military hardware and strategies. In sum, this study highlights the pivotal role of technology in warfare, offering insights for military strategists and the research community.